How does young adults’ dietary and health-related quality of life vary by food security and household income? - Kim, Eun-kyung; Kwon, Yong-Seok; Kim, Sena; Lee, Jin-Young; Park, Young Hee (Frontiers in Nutrition, 2024)
Objectives The objective of this study was to compare the dietary and health-related quality of life of young adults according to their household income and food security status. Methods To conduct this study, 10,224 young adults aged 19–34 years who participated in the 2008–2018 Korea National Health and Nutrition Examination Survey (KNHANES) were selected. Subjects were categorized into four groups based on household income and food security: ‘food secure and high income,’ ‘food insecure and high income,’ ‘food secure and low income,’ and ‘food insecure and low income’. General characteristics, daily diet, and dietary quality were compared among the four groups. Results The proportion of participants consuming a daily diet below the estimated average requirements for protein, vitamins A, B1, and B2, niacin, vitamin C, calcium, phosphorus, and iron increased in the ‘food insecure and low income’ group. Among the most commonly consumed foods, instant noodles and Sprite ranked relatively high in the ‘food insecure and low income’ group, while apples and beef ranked relatively high in the ‘food secure and high income’ group. The food insecure and low income group exhibited significantly increased rates of mobility problems [OR = 1.55(95% CI = 1.05–2.29)] and anxiety/depression [OR = 1.33(95% CI = 1.07–1.64)] in comparison with the food secure and high income group. Conclusion Food insecurity was positively associated with poor diet quality and was associated with health-related quality of life, mobility, and anxiety/depression, especially among young adults.